Social Activism and Societal Transformation: Assessing the Impact of Human Rights Movements - Ade Risna Sari; Gamar Al Haddar (Westscience Press, 2023)
This research employs bibliometric analysis to examine the impact of the Human Rights Movement on social activism and societal transformation. Through the utilization of the VOSviewer software, a systematic assessment of scholarly publications was conducted to uncover trends, collaborations, and influential works in this dynamic field. The analysis revealed distinct thematic clusters, including those centered around conflict, culture, business, health, and basic human rights. Seminal works, such as